A Snapshot Of Noise And Worker Exposures In Sand & Gravel Operations - E. R. Bauer (Society for Mining, Metallurgy & Exploration, 2008)
Previous studies and research efforts have shown that noise-induced hearing loss (NIHL) is a problem in the U.S. mining industry. This is especially true in surface and underground coal and stone mining where large, noisy equipment predominate. Workers in coal preparation and stone processing plants have also been found to be subject to high sound levels that could potentially cause NIHL over prolonged periods of exposure. National Institute for Occupational Safety and Health (NIOSH) researchers have been conducting a cross-sectional survey of equipment noise and worker noise exposures in the mining industry to estimate the potential for NIHL within the mining community. One commodity recently surveyed was the extraction of sand and gravel from surface pits and by river dredging. Little is known about the noise environment and worker exposures in these environments, where processing and mining equipment similar to coal and stone are employed. To address the potential for NIHL in the sand and gravel industry, sound levels on and around the dredges and processing equipment were recorded to identify areas of high noise levels. Full-shift worker dosimetry, in conjunction with task observations, was documented to determine the relationship between exposure and source. This paper presents research examining noise on dredges, in several surface mine sand and gravel operations and in the processing facilities. The locations where workers are likely to be overexposed and were found to be most susceptible to noise overexposures are reported. Results indicate that there are areas on the dredges (crane, suction pumps, and diesel engines) where sound levels greater than 90 dB(A) are present. In addition, crushers and screens used in the processing of the sand and gravel also generate sound levels greater than 90 dB(A). Although no surveyed worker exceeded the Mine Safety and Health Administration (MSHA) Permissible Exposure Level (PEL) of 90 dB(A) TWA8, laborers, mechanics, oilers, helpers, pickers, and greasers are the workers likely to be exposed to hazardous sound levels and thus develop NIHL over time. Knowledge of the equipment noise, area sound levels, and worker dose levels is information that management and employees can use to reduce exposures. Exposures can be reduced in certain areas through administrative controls and through engineering controls applied to the noisiest equipment.